IMPLEMENTASI BUILDING INFORMATION MODELING (BIM) DALAM PROSES TENDER PROYEK INFRASTRUKTUR - Faredzi Dhika Saputra (SINERGI : Jurnal Riset Ilmiah, 2026)
Building Information Modeling (BIM) is a digital approach capable of integrating planning, design, and construction information into a single unified model. The implementation of BIM in infrastructure projects in Indonesia continues to grow; however, its application at the tender stage is still not optimal. This study aims to analyze the implementation of BIM in the tender process of infrastructure projects and to identify the benefits and challenges encountered. The research method used is a qualitative descriptive method with a literature review approach and an analysis of BIM implementation practices at the tender stage. The results indicate that the use of BIM can improve the accuracy of tender documents, enhance efficiency in document preparation time, and increase transparency in the bid evaluation process. Nevertheless, BIM implementation still faces challenges, including limited human resources, high initial investment costs, and the absence of uniform national standards. This study is expected to serve as a reference for policy development and the implementation of BIM in the procurement process of infrastructure projects.